Hope and Haunting Images: The Imaginary in Danish Parkinson’s Disease Rehabilitation - Merete Tonnesen; Claus Vinther Nielsen (Medicine Anthropology Theory)
Much in life is imagined: hoped for, dreamed about, or dreaded, as we engage with potential futures. Parkinson’s disease is a progressive and neuro-degenerative disease, currently incurable. During long-term fieldwork among Danish rehabilitees with Parkinson’s disease, rehabilitees’ mentioning of hope and images of the future gradually inspired attention to an imaginary dimension in rehabilitation. We explore haunting images and hope among rehabilitees as examples of the imaginary in rehabilitation, but also as windows into how rehabilitees orientate themselves towards an uncertain future. We show how rehabilitees’ imaginations of the future resemble hauntings instigating an urge to ‘do something’ to avoid their actualisation; to insist on living in the now, keeping up training, and partaking in clinical trials. This urge translates into rehabilitation practices, where rehabilitees and professionals work with both hope and rehabilitation goals to maximise the present and postpone the future. We emphasise that hope is a complex phenomenon; it is multiple and has a certain elasticity. A person can carry multiple hopes at once; hope can be agentic, co-created and worked with, located, or be an existential stance.